Studi Kajian Pertumbuhan Penduduk di Kabupaten Deli Serdang - Romaito Aritonang; Luwy Berto Murbun; Rut Anatasya Simatupang; Zuliyansah; Dewi Mahrani Rangkuty (Lembaga Pengembangan Kinerja Dosen, 2023)
The total population of Deli Serdang, based on the results of the 2020 Population Census, is 1,931,441 people, including people with irregular residence, and is the second largest in North Sumatra after Medan City. While the population growth rate from 2020-2021, based on the last SP 2020 figure, is 0.69 percent per year, the total population of Deli Serdang in 2021 is estimated at 1,941,374 people with a population density of 777 people per Km2.